Bacterial Adaptation by a Transposition Burst of an Invading IS Element. (13th November 2021) - Miller, Scott R; Abresch, Heidi E; Ulrich, Nikea J; Sano, Emiko B; Demaree, Andrew H; Oman, Andrew R; Garber, Arkadiy I
Abstract: The general importance of transposable elements (TEs) for adaptive evolution remains unclear. This in part reflects a poor understanding of the role of TEs for adaptation in nonmodel systems. Here, we investigated whether insertion sequence (IS) elements are a major source of beneficial mutations during 400 generations of laboratory evolution of the cyanobacterium Acaryochloris marina strain CCMEE 5410, which has experienced a recent or on-going IS element expansion and has among the highest transposase gene contents for a bacterial genome. Most mutations detected in the eight independent experimental populations were IS transposition events. Surprisingly, however, the majority of these involved the copy-and-paste activity of only a single copy of an unclassified element (ISAm1) that has recently invaded the strain CCMEE 5410 genome. ISAm1 transposition was largely responsible for the highly repeatable evolutionary dynamics observed among populations. Notably, this included mutations in multiple targets involved in the acquisition of inorganic carbon for photosynthesis that were exclusively due to ISAm1 activity. These mutations were associated with an increase in linear growth rate under conditions of reduced carbon availability but did not appear to impact fitness when carbon was readily available. Our study reveals that the activity of a single transposase can fuel adaptation for at least several hundred generations but may also potentially limit the rate of adaptation through clonal interference.